Necesidad de reformar el art. 236 del código civil en el sentido que lesiona los derechos de legitimidad del padre en la acción para impugnar la paternidad - Díaz Uribe, Patricio Javier (2015)
The family as the primary form of social organization and core of every society mainly of Ecuador in its various forms legal effects; precisely like those of wedlock, cohabiting or union. Within this structure I can refer to the argument contesting paternity as the right of the alleged father or son to request the Court and annul the supposedly existing affiliation; thinking that this could be wrong or be unfair. In the Civil Code of our country had in the first paragraph of Article 236, states: “Any claim of the husband against the paternity of the child conceived by his wife during marriage, shall be made within sixty days from that he had knowledge of labor “. But there will be cases where concur deception by the spouse inducing registered as son to one that is not denying this way the child's right to know their true identity and father force assume a responsibility that does not belongs , therefore here a legal vacuum is created leaving defenseless the alleged father. Now through Official Gazette No. 526 dated June 9, 2015, it is currently conducted a reform of this body of law, where some items, especially Art. 236 repealing, introducing some reforms regarding the problem in Art. 233 where it states that the child born after the expiration of one hundred eighty subsequent marriage days , is said to be conceived in , and can impute paternity by DNA examination, but not the word , term or set a period of time to challenge paternity , ie there is still a legal vacuum. Given this, it should be mentioned that Art. 1474 of the Civil Code “The fraud does not vitiate consent when it is the work of a party , as also shown clearly that without him would not have hired " and that this is closely related art. 32 of the Civil Code, which states "presumption is called the consequence that follows from certain backgrounds or circumstances known. If that background or circumstances giving rise to the presumption are determined by law, the presumption is called legal”. Causing an illegal financial obligation for life. I mean, according to this rule, who has discovered the infidelity and the son whom he has recognized as yours is not. You restricts the spouse to achieve present this judicial operation, subsequently after sixty days in the case of article repealed mentioned above and also as in the case of the new effect, whereby the right to bring legal action is violated, are transgressing constitutional rights mentioned by the Constitution of the Republic regarding verbatim in Article 75: a) no one shall be deprived of the right to defense at any stage or grade of the procedure. b) Having the appropriate time and facilities for the preparation of his defense; c) Be heard in a timely manner and on an equal footing. What this is a Recording in inapplicability of the law; this means that in a democratic state of law must be no more legal violence of the strictly imposed the paragraph recognizing other forms of abuse, undoubtedly Legal